2011
DOI: 10.1038/gt.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune hearing loss is exacerbated in IL-10-deficient mice and reversed by IL-10 gene transfer

Abstract: Interleukin-10 (IL-10) has an important role in the homeostatic regulation of autoreactive T-cell repertoire. We hypothesized that endogenous IL-10 would regulate the severity of b-tubulin-induced experimental autoimmune hearing loss (EAHL) and that exogenous IL-10 would abrogate it. BALB/c wild-type (WT) and homozygous IL-10-deficient mice (IL-10 À/À ) underwent b-tubulin immunization to develop EAHL; some IL-10 mice with EAHL were administered IL-10 DNA at the peak of EAHL. Auditory brainstem responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It has been suggested that interleukin-10 (IL-10) could be involved in controlling the level of the inflammatory response. In particular, autoimmune hearing loss is intensified in IL-10 deficient mice and this response is reversed by IL-gene transfer (Zhou et al, 2012), and the early phase of cochlear inflammation in a murine model, before the recruitment of leukocytes and macrophages, is significantly exacerbated by IL-10 deficiency (Woo et al, 2015). A second way to protect the auditory organ would be to enhance the resolution phase of inflammatory responses.…”
Section: Lds In the Cochlea: Part Of An Anti-inflammatory Mechanism?mentioning
confidence: 99%
“…It has been suggested that interleukin-10 (IL-10) could be involved in controlling the level of the inflammatory response. In particular, autoimmune hearing loss is intensified in IL-10 deficient mice and this response is reversed by IL-gene transfer (Zhou et al, 2012), and the early phase of cochlear inflammation in a murine model, before the recruitment of leukocytes and macrophages, is significantly exacerbated by IL-10 deficiency (Woo et al, 2015). A second way to protect the auditory organ would be to enhance the resolution phase of inflammatory responses.…”
Section: Lds In the Cochlea: Part Of An Anti-inflammatory Mechanism?mentioning
confidence: 99%
“…IL10 is a cytokine synthesis inhibitory factor and a co-stimulator for the proliferation and differentiation of T and B mast cells [ 87 , 88 ]. For the relationships between IL10 and MD, although no direct relationships between such genes and the disease have been reported, a specific report on autoimmune hearing loss validated that the abnormal secretion of IL-10 may contribute to specific hearing loss symptoms of experimental autoimmune hearing loss [ 89 ]. Because hearing loss is a typical symptom of MD, which is also widely considered an autoimmune disorder, it is quite reasonable that IL10 may also participate in the pathological processes of MD [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of autoimmune hearing loss are generated by immunization with β-tubulin, one of the inner ear antigens (Cai et al 2009;Zhou et al 2011). In a study by Zhou et al (2012), autoimmune hearing loss was induced by immunization against β-tubulin in mice that are deficient in interleukin-10 (IL-10) (Zhou et al 2012). IL-10 is a cytokine ( Table 1) that mediates its anti-inflammatory actions by inhibiting the production of proinflammatory cytokines involved in monocyte/macrophage activation (Anderson et al 2004;Maynard & Weaver 2008).…”
Section: Gene Therapy and Autoimmune Inner Ear Diseasementioning
confidence: 99%